Revitalization of the Function of Satlinmas in the Implementation of Minister of Home Affairs Regulation Number 84 of 2014 from the Perspective of Fiqh Siyāsah Tanfīdziyah - M. Yudi Setiawan; Fathul Mu'in; Rudi Santoso (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2026)
The Community Protection Unit (Satlinmas) is a strategic regional government apparatus in maintaining public order, peace, and community protection. The existence of Satlinmas is specifically regulated in the Regulation of the Minister of Home Affairs Number 84 of 2014 concerning the Implementation of Community Protection. This study aims to analyze the role of Satlinmas in the implementation of the Ministerial Regulation and examine it from the perspective of fiqh siyāsah tanfīdziyah. This research employs a library research method using normative-juridical and siyasah syar‘iyyah approaches. Data were collected through the study of legislation, classical fiqh siyasah literature, scientific journals, and other relevant academic sources The research results show that Satlinmas plays a crucial role in protecting the community through security, disaster management, and the maintenance of public order. However, the implementation of the Minister of Home Affairs Regulation Number 84 of 2014 still faces challenges, including limited human resources, limited training, weak coordination, and insufficient budget support. From the perspective of Fiqh Siyāsah Tanfīdziyah, the existence of Satlinmas aligns with the principles of siyāsah syar‘iyyah in maintaining public welfare, public security, and fulfilling the government’s mandate and responsibility towards the people. Therefore, optimizing Satlinmas is crucial to support effective regional governance that is oriented towards the public welfare.